2003
DOI: 10.1016/s1526-9523(03)00277-0
|View full text |Cite
|
Sign up to set email alerts
|

Ice Massage for the Reduction of Labor Pain

Abstract: The current study investigated the use of ice massage of the acupressure energy meridian point large intestine 4 (LI4) to reduce labor pain during contractions. LI4 is located on the medial midpoint of the first metacarpal, within 3 to 4 mm of the web of skin between the thumb and forefinger. A one‐group, pretest, posttest design was chosen, which used 100‐mm Visual Analog Scales (VAS) and the McGill Pain Questionnaire (MPQ) ranked numerically and verbally to measure pain levels; the pretest served as the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 22 publications
3
49
0
6
Order By: Relevance
“…Studies by Enjezab et al, 7 and Waters et al 13 showed that using ice massage on the Hugo point decreased pain intensity 30 minutes after intervention. , In addition, Fan Qu studied the effect of electro-acupuncture on points L14 and SP6 on the intensity of labor and concluded that the technique could cause reduction in pain during the active phase.…”
Section: Discussionmentioning
confidence: 97%
“…Studies by Enjezab et al, 7 and Waters et al 13 showed that using ice massage on the Hugo point decreased pain intensity 30 minutes after intervention. , In addition, Fan Qu studied the effect of electro-acupuncture on points L14 and SP6 on the intensity of labor and concluded that the technique could cause reduction in pain during the active phase.…”
Section: Discussionmentioning
confidence: 97%
“…Alternative labor analgesia techniques such as water birth, 141 acupuncture and acupressure, 142,143 and ice massage at acupressure points 144 have been suggested to reduce labor pain and the use of analgesics. To date, few reports compare these alternative modalities to central neuraxial analgesia.…”
Section: Analgesia For Labor and Deliverymentioning
confidence: 99%
“…The comfort measures like ice massage at energy meridian point called large intestine 4 pathway moves from the tip of the fore finger to the face and then it encircles the teeth. Later, it bifurcates at the shoulder and moves downward wrapping around the entire colon [4]. During pregnancy term, the colon practically encircles the upper portion of the uterus.…”
Section: Introductionmentioning
confidence: 99%